Comparative Study of Dantyadi lepa and Swarjik Ksharadi Lepa in the Management of Stanagranthi w.s.r. to Fibroadenosis of Breast - Shedad Sachin Ladak; Roy Anuradha; Shiv Ji Gupta; Ruchi Chawla; Binay Sen (AYUSHDHARA, 2025)
Fibroadenosis, a benign breast condition common in women of reproductive age, is characterised by glandular and stromal tissue proliferation, leading to lumps. It is hormone-dependent, causing pain, swelling, and psychological distress. The rising global incidence emphasises its importance as a public health concern. Review in Ayurveda and Modern Medicine: In Ayurveda, fibroadenosis is similar to ‘Stana-granthi.’ Modern treatment involves conservative and surgical approaches, which may have side effects or high recurrence rates, highlighting the need for alternative therapies. Drug Review: Dantyadi Lepa (DL) and Swarjika Ksharadi Lepa (SL) are Ayurvedic formulations with lump-reducing and scraping properties. DL contains Danti, Chitraka root, Arka latex, and Kasisa, while SL contains Swarjika Kshara, MulakaKshara, and Shankha Bhasma. Both target Kapha and Vatadoshas to address fibroadenosis. Materials and Methods: 40 patients were divided into two groups: Group 1 (DL) and Group 2 (SL), with both treatments applied twice daily for 2 months. Four follow-ups were conducted at 15-day intervals. Observations and Results: Group 1 (DL) showed 74.5 % cured, while Group 2 (SL) showed 67.4 % cured. Overall, 71.2% of patients experienced significant symptom relief. Discussion and Conclusion: Both DL and SL were effective in reducing pain, swelling, and mass size, offering a promising, non-invasive alternative to conventional treatments. Their safety and efficacy suggest they are viable options for managing fibroadenosis.